Evaluation of a mentorship matchmaking event at an academic research institution to reinforce the scientific workforce pathway for underrepresented minority groups - Sirena Gutierrez; Jennifer A. Seuferer; Angel-Max Guerrero; Yazmin Carrasco; Kirsten Bibbins-Domingo; Tung Nguyen; Leticia Márquez-Magaña; Todd Nystul; Meghan D. Morris (BMC Medical Education)
Abstract Background Mentorship and research experiences are crucial for STEMM career entry and advancement. However, systemic barriers have excluded people from historically underrepresented groups. Methods In 2021, a virtual “matchmaking event” was held to connect NIH-funded research mentors with historically underrepresented trainees and initiate mentored research experiences. Survey data collected over 12 months was analyzed to evaluate the program’s success considering the number of mentor-trainee connections, mentor-trainee research experience matches, and NIH diversity supplement application status. Statistical tests, including student’s t-test, ANCOVAs, and chi-square tests, evaluated differences between attendee groups and survey time points. Results Out of 314 mentors contacted and 99 registered trainees, 113 mentors and 92 trainees participated. Among mentors (n = 73), 53% identified as women, 56% as non-Hispanic white, and a majority (81%) reported being the first in their family to attend college. Among trainees (n = 79), about two-thirds (67%) identified as women, 47% identified as Hispanic/Latinx, and 15% identified as Black/African American. Both mentors and trainees were extremely satisfied with the overall event (57% and 69%, respectively) and would recommend it to others (74% and 90%, respectively). Most mentor participants established at least one mentor-trainee connection after the event (n = 64, 57%), a mentor-trainee research experience match (n = 40, 35%), and planned to submit an NIH diversity supplement (n = 31, 27%). Many trainees obtained paid positions through the mentor-trainee research experience. One year after the event, 11 trainees secured NIH diversity supplement funding with their mentors. Conclusions The matchmaking event began bridging a much-needed gap in the research pathway by creating opportunities for trainees to connect with mentors and obtain funded research opportunities.